Publicznoprawne instrumenty „demokracji walczącej” w polskim systemie prawa - Janiak, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The Polish system of public law has legal mechanisms that reflect the idea of a militant democracy, assuming the need to equip the democratic system with instruments that will allow it to defend itself against actions aimed at its annihilation. They appear both on the constitutional level and in the acts of administrative and criminal law. As a result, the problem of the instruments of militant democracy becomes an interdisciplinary issue. The conducted analysis shows that the instruments in question, in spite of appearances, have a lot in common. Their use causes similar problems, the source of which are, among others, disputes arising around the concepts of Nazism, fascism,communism and totalitarianism.
Keywords: totalitaryzm; komunizm; faszyzm; nazizm